A modified 3D printer as a hybrid bioprinting-electrospinning system for use in vascular tissue engineering applications. (August 2021) - Fazal, Faraz; Diaz Sanchez, Francisco Javier; Waqas, Muhammad; Koutsos, Vasileios; Callanan, Anthony; Radacsi, Norbert
Highlights: Hybrid bioprinting is an attractive technique to meet the urgent need for small-diameter vascular grafts. The electrospun nanofibers can be used to reinforce the vascular grafts made from hydrogels. A commercially available 3D printer is modified to a hybrid bioprinting and electrospinning setup. The hybrid setup has the capability to fabricate tubular vascular constructs. Abstract: There is a high demand for small diameter vascular grafts having mechanical and biological properties similar to that of living tissues. Tissue-engineered vascular grafts using current methods have often failed due to the mismatch of mechanical properties between the implanted graft and living tissues. To address this limitation, a hybrid bioprinting-electrospinning system is developed for vascular tissue engineering applications. The setup is capable of producing layered structure from electrospun fibres and cell-laden hydrogel. A Creality3D Ender 3D printer has been modified into a hybrid setup having one bioprinting head and two electrospinning heads. Fortus 250mc and Flashforge Creator Pro 3D printers were used to print parts using acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA) polymers. An Arduino mega 2560 and a Ramps 1.4 controller board were selected to control the functions of the hybrid bioprinting setup. The setup was tested successfully to print a tubular construct around a rotating needle.